The Second Passover, Pilgrimage, and the Centralized Cult - Chavel, Simeon (Harvard theological review, 2009)
The passage in Numbers 9:1-14 presents new legislation on the Passover sacrifice. For one who contracted impurity immediately prior to the Passover or was too far away to participate in it, the amendment prescribes an alternate date, one month later: When any of you or your posterity who are defiled by a corpse or are on a long journey would offer a passover sacrifice to the Lord, they shall offer it in the second month, on the fourteenth day of the month, at twilight (vv. 10-11).